Respuesta :
1st disribute .4 through the parentheses.
.4 (.3x-1)=2+.75x
.12x-.4=2+.75x
subtract .12x from each side
-.4 = 2 + .63x
subtract 2 from each side
-2.4 = .63x
Divide each side by .63
-3.81 = x
.4 (.3x-1)=2+.75x
.12x-.4=2+.75x
subtract .12x from each side
-.4 = 2 + .63x
subtract 2 from each side
-2.4 = .63x
Divide each side by .63
-3.81 = x
0.12x - 0.4 = 2 + 0.75x
0.12x - 0.75 x = 2 + 0.4
-0.63 x = 2.4
x = 2.4/-0.63
x = - 3.8
0.12x - 0.75 x = 2 + 0.4
-0.63 x = 2.4
x = 2.4/-0.63
x = - 3.8